DENSITY ANALYSIS OF RIVER WATER THROUGHOUT JAKARTA CITY TO HYDROSTATIC PRESSURE - Tri Wulan Sari; Denny Yatmadi (UNIVERISTAS PGRI MADIUN, 2021)
Different activities of a river area, can caused differences in density and hydrostatic pressure of the fluid contained in rivers in different places. This study aims to analyze the relationship between density and hydrostatic pressure fluid of 5 rivers that cross Jakarta and empties into Jakarta Bay. Laboratory testing is carried out using the Center of Pressure tool. The data obtained after the test are mass, weight, moment, and Perspex water level. The data were analyzed using the appropriate formula to obtain the density of water from 5 research locations. Then continued the analysis of the hydrostatic pressure at the research site. The results obtained indicate that the hydrostatic pressure is directly proportional to the density of the liquid. Like the hydrostatic pressure in Sunter drain, the highest hydrostatic pressure among the others is 10389.24 N/m2, with the highest density of water also being 1060.13 kg/m3.Keywords : River; fluid; center of pressure ; Density; Hydrostatics pressure.